Sleep apnea: Tracking effects of a first session of CPAP therapy by means of Granger causality. (April 2020) - Orjuela-Cañón, Alvaro D.; Cerquera, Alexander; Freund, Jan A.; Juliá-Serdá, Gabriel; Ravelo-García, Antonio G.
Highlights: Granger causality quantifies connectivity of a brain-heart network in apnea patients. In brain subsystems, connectivity from theta to beta decreases in apnea patients. Apnea decreases connectivity among subsystems given by heart rate variability. Continuous positive air pressure therapy restores brain-heart network in a first term. Abstract: Connectivity between physiological networks is an issue of particular importance for understanding the complex interaction brain-heart. In the present study, this interaction was analyzed in polysomnography recordings of 28 patients diagnosed with obstructive sleep apnea (OSA) and compared with a group of 10 control subjects. Electroencephalography and electrocardiography signals from these polysomnography time series were characterized employing Granger causality computation to measure the directed connectivity among five brain waves and three spectral subbands of heart rate variability. Polysomnography data from OSA patients were recorded before and during a first session of continuous positive air pressure (CPAP) therapy in a split-night study. Results showed that CPAP therapy allowed the recovery of inner brain connectivities, mainly in subsystems involving the theta wave. In addition, differences between control and OSA patients were established in connections that involve lower frequency ranges of heart rate variability. This information can be potentially useful in the initial diagnosis of OSA, and determine the role of cardiac activity in sleep dynamics based on the use of three subbands of heart rate variability.